Prototype of Rainfall Intensity Measurement Using CCD TSL1401CL Linear Sensor Array - Deswilan, Sixtinah; Costrada, Aldo Novaznursyah; Harmadi, Harmadi (Universitas Andalas, 2021)
A prototype measurement of rainfall intensity was developed using a CCD TSL1401CL linear sensor array. The prototype consists of a He-Ne laser that functions as a light source, which later is focused by the beam expander and conditioned by a convex lens. Each pixel will receive the same voltage depending on the light intensity so that it produces a decimal value of ADC. This ADC decimal value determines rainfall intensity based on the diameter and velocity of the raindrops. The diameter variations used ranges from 1 mm to 10 mm, while for variations in the height of rainfall are 50 cm, 100 cm, and 150 cm. The test results proved that the greater the decimal value of the ADC is, the smaller the diameter of the raindrops detected will be, and vice versa. The values of the diameter and velocity of were used to obtain the value of rainfall intensity. The percentage value of error measuring rainfall intensity is 3.11% when compared to the rain gauge module is still considered rather accurate. However, direct testing is still needed when rain falls with various types and intensities. Â